Inside Back Cover: Chemical Characterization of a Volatile Dubnium Compound, DbOCl3 (Angew. Chem. Int. Ed. 33/2021). Issue 33 (14th June 2021) - Chiera, Nadine M.; Sato, Tetsuya K.; Eichler, Robert; Tomitsuka, Tomohiro; Asai, Masato; Adachi, Sadia; Dressler, Rugard; Hirose, Kentaro; Inoue, Hiroki; Ito, Yuta; Kashihara, Ayuna; Makii, Hiroyuki; et al.
Abstract : Extreme gas‐phase chemistry with the exotic transactinide dubnium and its lighter homologues tantalum and niobium is described by Nadine M. Chiera, Tetsuya K. Sato, and co‐workers in their Communication on page 17871 . The sequence of volatility among Group 5 elements, as deduced from the behavior of their oxychloride compounds, is in agreement with Mendeleev's law, establishing dubnium as one of the least volatile elements of the periodic table.